Implementasi dan Implikasi Sosialisasi Empat Pilar Berbangsa Dan Bernegara Pasca Putusan Mahkamah Konstitusi - Andra Bani Sagalane (Universitas Jayabaya, 2015)
Four Pillars of Nation and State is Pancasila, the Constitution of the Republic of Indonesia in 1945, national unity and the Republic of Indonesia which is articulated by members of the DPR/MPR to the public. This idea is included in item Law of Political Parties that have strong legitimacy. The four pillars of the state and nation reap the pros and cons in the community, especially among experts in constitutional law of the State. The experts have similar views to criticize the concept of it because it is not considered appropriate if it is aligned as the four pillar or column country. The Constitutional Court issued a decision removing the article. The Constitutional Court’s decision is binding and must be executed by all parties. That is the four pillars of the nation and state is forbidden to be disseminated to the public, but the reality is different, the constitutional court ruling was ignored by the DPR/MPR until today. They continue to socialize the four pillars. That is the institution DPR/MPR may be unlawful.